A randomized trial of endometrial scratching in women with PCOS undergoing ovulation induction cycles. Issue 2 (February 2022) - Glanville, Elizabeth Joan; Wilkinson, Jack; Sadler, Lynn; Wong, Tze Yoong; Acharya, Santanu; Aziz, Nabil; Clarke, Fiona; Das, Sangeeta; Dawson, Jeanette; Hammond, Bev; Jayaprakasan, Kanna; Milner, Matthew; et al.
Abstract: Research question: Does endometrial scratching improve the chance of a live birth in women with polycystic ovary syndrome (PCOS) undergoing ovulation induction and trying to conceive? Design: An international, multicentre, randomized, sham-controlled trial across six fertility clinics in three countries (New Zealand, UK and Brazil). Women with a diagnosis of PCOS who were planning to commence ovulation induction cycles (at least three cycles) in order to conceive were randomly assigned to receive the pipelle (scratch) procedure or a sham (placebo) procedure in the first cycle of ovulation induction. Women kept a diary of ovulation induction and sexual intercourse timing over three consecutive cycles and pregnancies were followed up to live birth. Primary outcome was live birth and secondary outcomes were clinical pregnancy, ongoing pregnancy, multiple pregnancy, adverse pregnancy outcomes, neonatal outcomes, bleeding following procedure and pain score following procedure. Results: A total of 117 women were randomized; 58 to the scratch group and 59 to the sham group. Live birth occurred in 11 (19%) women in the scratch group and 14 (24%) in the sham group (odds ratio 0.76, 95% confidence interval [CI] 0.30–1.92). Secondary outcomes were similar in each group. Significantly higher pain scores were reported in the scratch group (adjusted mean difference 3.2, 95% CI 2.5–3.9) when measured on a visual analogue scale. Conclusion: No difference was detected in live birth rate for women with PCOS who received an endometrial scratch when trying to conceive using ovulation induction; however, uncertainty remains due to the small sample size in this study.